Input‐parallel output‐series DC–DC converter for non‐isolated high step‐up applications. Issue 20 (7th September 2016) - Hu, Xuefeng; Li, Linpeng; Li, Yongchao; Wu, Guiyang
Abstract : A high voltage conversion ratio interleaved boost converter is proposed with connecting input in parallel and output in series. By introducing coupled‐inductor and diode‐capacitor techniques, the converter can further extend the voltage gain. Because of the interleaved structure, the input current ripple can be reduced significantly, alleviating the electromagnetic interference problem. The test results of a 200 W prototype are provided and high efficiency above 93.5% is achieved.